Application of Luffa Cylindrica in Natural form as Biosorbent to Removal of Divalent Metals from Aqueous Solutions - Kinetic and Equilibrium Study - Oboh, Innocent O.; Aluyor, Emmanuel O.; Audu, Thomas O. K. (IntechOpen, 2011)
None